O konieczności nauczania liczb rzeczywistych i trygonometrii hiperbolicznej w kontekście użycia programu Matlab - Janaszak, Tadeusz (Some remarks about the necessity of teaching about complex numbers and hiperbolic trigonometry in the context of Matlab programme, 2009)
The text is an appeal to return the teaching of complex numbers and trigonome-try to the economic schools; without these branches it is impossible to working with the program Matlab
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 99-110
Keywords: hyperbolic trigonometry; complex number; program Matlab